Interaction With In-Vehicle Infotainment Systems - Development of Interaction Tools For In-Vehicle Infotainment Systems During Low-Levels of Automation In Rural Environments - ARVIDSSON, JONAS; GRANSTRÖM, JONATHAN (My University, 2018)
Increasingly more car manufacturers are implementing advanced driver-assistance systems in vehicles. Furthermore, the rise of smart devices has created an environment where people expect more of their devices to be connected to the internet. As a result, the infotainment systems in vehicles are becoming more connected and provide more functionality, e.g., direct messaging. This thesis presents a concept which allows a driver to interact with the communicative tasks of an infotainment system in both non- and partially automated vehicles, driven in rural environments. The concept consists of a trackpad placed to the side of the driver, in an arm rest position, which acts as the input device. A head-up display placed in the front window of the vehicle is used as the output. We believe the concept shows promise, but requires more development in certain areas, such as text-input, and more thorough evaluation in real life environments, in order to properly confirm if the concept is safe enough to use in a vehicle when driving.
Keywords: automotive; interaction design; human-machine interface; autonomous; infotainment; user interface